African SMEs Innovation Challenges - (:unkn) unknown (My University, 2023)
Internationally, small and medium manufacturing businesses (SMEs) are widely acknowledged as a significant source of employment and the cornerstone of a prosperous entrepreneurial ecosystem. Due to their sizeable contribution to the gross domestic product (GDP) of any nation, they can also be seen to a large extent as an economic transformation's catalyst. For any nation seeking change, poverty reduction, employment redistribution, corporate innovation, and robust economic growth, SME become the point of reference, as they have been praised as the national key asset. Manufacturing growth due to SMEs has gotten stronger in nations including the United States, China, the Czech Republic, Japan, and Australia, suggesting that any anticipated worldwide decline in industrial production may be tempered by their contribution. This proves beyond a shadow of a doubt that manufacturing SMEs play a crucial role in any nation, but maybe more so in developing African nations. However, the declining GDP contribution of manufacturing SMEs in Africa has deeply concerned investors, policymakers, and academics. As a result, more research into the problems facing manufacturing SMEs is required in order to provide support that will seek to provide innovative sustainable measures for the sustainable growth of these important businesses.
Keywords: African Research